Revisiting agricultural finance: A special report from the fin4ag conference - July 2014 - TXF (TXF, 2014)
This special report was produced on agricultural financing for the landmark Fin4Ag conference in Nairobi. The report seeks to highlight some of the challenges and opportunities that producers, traders, banks and other financiers face in a sector that is fast transforming itself. With mobile technology, commodity exchanges and new financing tools revolutionising agriculture in African, Caribbean and Pacific countries, it is time for international commercial banks, insurers and collateral managers to take a second look.